Crystallisation parameters effect on the particle size distribution (PSD) of carbamazepine-saccharin (CBZ-SAC) co-crystals in batch cooling crystallisation - E N, Engku Mat Nasir; F, Ab Rahman; Syarifah, Abd Rahim; R Z, Edros; N., Anuar (IOP Publishing Ltd, 2020)
Abstract. The crystallisation parameters effect on the particle size distribution (PSD) of carbamazepine-saccharin (CBZ-SAC) co-crystals in batch cooling crystallisation is presented.The particle size distribution study of CBZ-SAC co-crystals revealed that the multimodal with broad PSD was found for CBZ concentration of 19.14 mg/ml. Meanwhile, the unimodal with broad PSD were observed at CBZ concentration of 17.01 mg/ml and 17.96 mg/ Crystal characterisation using differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), Fourier transform infrared (FTIR) and optical microscopy confirm the solid formed is CBZ-SAC co-crystal Form I with plate-like crystal morphology.